Rancang Bangun Sistem Informasi Pelaporan Luas Tambah Tanam dan Panen Berbasis Web - Wiwisnawati, Wiwisnawati; Hartono, Nahrun; Baharuddin, Hastuti (Jurusan Sistem Informasi Universitas Islam Negeri Alauddin Makassar, 2023)
The reporting process at the Agricultural Extension Center takes quite a long time due to the distance from each village, where getting report data to the office to collect reports is quite far, and the media for collecting reports are still conventional. From these problems, the researcher aims to create a planting area reporting information system and a harvest-based website that can assist in collecting, processing, storing, and presenting data reports and assist extension coordinators in making decisions and planning. This study uses qualitative research, data collection methods of observation, interviews, and literature. The system design method uses a waterfall. System testing uses the Black Box, and system feasibility testing uses the System Usability Scale (SUS) method. The results of the study are in the form of a website application where from the results of the system feasibility test, an average value of 80.1 is obtained; on the grade scale assessment, they get a grade